Multidisciplinary team healthcare professionals' perceptions of current and optimal acute rehabilitation, a hip fracture example A UK qualitative interview study informed by the Theoretical Domains Framework. - Stefanny Guerra; Kate Lambe; Gergana Manolova; Euan Sadler; Katie J Sheehan (PLoS ONE)
Objective To understand multidisciplinary team healthcare professionals' perceptions of current and optimal provision of acute rehabilitation, perceived facilitators and barriers to implementation, and their implications for patient recovery, using hip fracture as an example. Methods A qualitative design was adopted using semi-structured telephone interviews with 20 members of the acute multidisciplinary healthcare team (occupational therapists, physiotherapists, physicians, nurses) working on orthopaedic wards at 15 different hospitals across the UK. Interviews were audio-recorded, transcribed verbatim, anonymised, and then thematically analysed drawing on the Theoretical Domains Framework to enhance our understanding of the findings. Results We identified four themes: conceptualising a model of rehabilitative practice, which reflected the perceived variability of rehabilitation models, along with facilitators and common patient and organisational barriers for optimal rehabilitation; competing professional and organisational goals, which highlighted the reported incompatibility between organisational goals and person-centred care shaping rehabilitation practices, particularly for more vulnerable patients; engaging teams in collaborative practice, which related to the expressed need to work well with all members of the multidisciplinary team to achieve the same person-centred goals and share rehabilitation practices; and engaging patients and their carers, highlighting the importance of their involvement to achieve a holistic and collaborative approach to rehabilitation in the acute setting. Barriers and facilitators within themes were underpinned by the lack or presence of adequate ways of communicating with patients, carers, and multidisciplinary team members; resources (e.g. equipment, staffing, group classes), and support from people in leadership positions such as management and senior staff. Conclusions Cornerstones of optimal acute rehabilitation are effective communication and collaborative practices between the multidisciplinary team, patients and carers. Supportive management and leadership are central to optimise these processes. Organisational constraints are the most commonly perceived barrier to delivering effective rehabilitation in hospital settings, which exacerbate silo working and limited patient engagement.